2007
DOI: 10.1203/pdr.0b013e3180a76d94
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Double Blind Controlled Trial on Effects of Long-Term Consumption of Fermented Milk Containing Lactobacillus casei in Pre-School Children With Allergic Asthma and/or Rhinitis

Abstract: ABSTRACT:To examine whether long-term consumption of fermented milk containing a specific Lactobacillus casei may improve the health status of preschool children suffering from allergic asthma and/or rhinitis a randomized, prospective, double blind, controlled trial was conducted in 187 children 2-5 y of age. The children received for 12 mo either fermented milk (100 mL) containing Lactobacillus casei (10 8 cfu/mL) or placebo. The time free from and the number of episodes of asthma/rhinitis after starting inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 30 publications
3
141
1
8
Order By: Relevance
“…The duration of the probiotic treatment may also be of importance. A clinical trial on probiotics in preschool children showed that fewer rhinitis episodes occurred in the latter half of the study, indicating that probioticinduced modulation might depend on longer treatment periods [8]. The majority of the studies with probiotics for rhinological symptom improvement have been done in patients with seasonal or perennial allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the probiotic treatment may also be of importance. A clinical trial on probiotics in preschool children showed that fewer rhinitis episodes occurred in the latter half of the study, indicating that probioticinduced modulation might depend on longer treatment periods [8]. The majority of the studies with probiotics for rhinological symptom improvement have been done in patients with seasonal or perennial allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Some controlled trials reported overall positive results with the administration of lactobacillus in children with AR [108,109], and a small study reported clinical and anti-inflammatory effects provided by Bacillus clausii [110]. Data showing that probiotic supplementation modulates immune responses in AR and may potentially alleviate the AR symptom severity [111] are encouraging, but their primary preventive effect on atopic diseases, probably by enhancing the T helper type 1 (TH1) response, is still unconfirmed [112].…”
Section: Other Interventionsmentioning
confidence: 99%
“…Based on the impact of intestinal microbiota modifications on food allergies, new dietetic strategies are currently being proposed, including the addition of prebiotics and probiotics to hydrolyzed infant formulae to prevent atopic diseases (Wold, 1998;Isolauri et al, 2000;Kalliomaki et al, 2001;Rosenfeldt et al, 2003;Viljanen et al, 2005;Giovannini et al, 2007;Kukkonen et al, 2007;Betsi et al, 2008;Boehm and Moro, 2008). Nonetheless, their efficacy and tolerance has still not been proven (FAO/WHO, 2002;AFSSA, 2003;Agostoni et al, 2004Agostoni et al, , 2007Osborn and Sinn, 2007;Hol et al, 2008;Kopp et al, 2008;Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%